Pemanfaatan Kulit Kakao menjadi Produk Kerupuk sebagai Solusi Gagal Panen Perkebunan Kakao di Desa Karang Radja - Vera Khoirunisa; Muhammad R. Ramanda; Dina Fithriyani; Sefrani Siregar (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Cocoa is one of the highly valuable commodities in the Indonesian economy. In terms of its contribution to the nation's foreign exchange, cocoa comes in third. Nevertheless, the farmers' livelihoods in the village of Karang Raja, South Lampung Regency, have been impacted by the failure of the cocoa crop in 2020 and 2021. One way to prevent crop losses and lower the high cocoa shell waste in Karang Radja village is to use the leftover cocoa shells. With the help of this community service program, the residents of the village of Karang Radja will receive training on how to turn leftover cocoa shells into crackers. Surveys are conducted as part of the implementation process, and tools and materials are prepared as well as training in the cracker production.